1990
DOI: 10.1210/endo-126-2-1096
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Reduction in Pancreatic Glucagon with Normalization of Somatostatin and Decrease in Insulin in Normoglycemic Alloxan-Diabetic Dogs: A Putative Mechanism of Glucagon Irresponsiveness to Hypoglycemia*

Abstract: In alloxan-diabetic (A-D) dogs, plasma glucagon does not increase when glycemia is decreased by insulin. Therefore, as in insulin-dependent diabetes mellitus (IDDM), increased glucose utilization is not matched by an increase in hepatic production. To explore further the abnormal effects of insulin on regulation of pancreatic glucagon, we studied content and morphology of pancreatic hormones in six normal (N) dogs, five hyperglycemic A-D (HD) dogs, and in four A-D dogs where normoglycemia was maintained by ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Decrease number of islets in pancreatic tissue observed in diabetic rats could be due to conversion of large islets to small. Reduction of numbers and volume density of islets by 70% was also reported in diabetic dogs (Sudha Rastogi et al, 1990). The histopathological study of diabetic treated groups indicates; increase volume density of islets, percent of β cells and size of islet in the group received walnut leaf, which may be a sign of regeneration.…”
Section: Discussionmentioning
confidence: 53%
“…Decrease number of islets in pancreatic tissue observed in diabetic rats could be due to conversion of large islets to small. Reduction of numbers and volume density of islets by 70% was also reported in diabetic dogs (Sudha Rastogi et al, 1990). The histopathological study of diabetic treated groups indicates; increase volume density of islets, percent of β cells and size of islet in the group received walnut leaf, which may be a sign of regeneration.…”
Section: Discussionmentioning
confidence: 53%
“…Immunohistochemical studies demonstrated that the pancreas from alloxan-induced diabetic animals showed a 70% reduction of beta cell areas. At the same time, there was an increase in the areas occupied by delta cells and no alteration in glucagon-producing cells [29] . Another study [30] showed decreases in the number of insulin positive cells and increases in the number of cells expressing somatostatin in rats submitted to alloxan-induced diabetes.…”
Section: -------------------------------------------------------mentioning
confidence: 83%
“…However, the beneficial effect of SST on glucose homeostasis does not appear to extend across species (or experimental models). Specifically, continuous treatment of severely diabetic Balb/C mice with octreotide did not influence blood glucose or insulin levels, however it reduced GH hypersecretion and prevented the proliferation of kidney glomeruli (Rastogi et al, 1990). Octreotide did not reduce hyperglycemia in alloxan-diabetic male Wistar rats, however a reduction of kidney weight without normalization of the glomerular filtration rate was reported (Usenmez et al, 2000).…”
Section: Type 1 Diabetes Mellitus -Early Studies Have Demonstrated Thmentioning
confidence: 98%
“…Administration of insulin also reduced the elevated levels of pancreatic SST and glucagon content in Sprague-Dawley (Papachristou et al, 1989) and Wistar (Kadowaki et al, 1980) rats with streptozotocininduced diabetes and in dogs with alloxan-induced diabetes (Rastogi et al, 1990). It is important to note that at least in animal models with chemically-induced type 1 diabetes, pancreatic D-cells show reduced or no response to increased glucose, which may explain the inadequate increase of SST secretion following food ingestion (Grill and Efendic 1983;Hermansen 1981).…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%